Inequality of Opportunities in the Labor Market : Evidence from Life in Transition Surveys in Europe and Central Asia - Abras, Ana; Hoyos, Alejandro; Narayan, Ambar; Tiwari, Sailesh (World Bank, Washington, DC, 2013)
This paper attempts to quantify the degree of inequality of opportunity in labor market outcomes for a selection of countries in the Europe and Central Asia (ECA) region. We adapt the Human Opportunity Index (HOI) methodology that has been widely used to study opportunities of children to measures of inequality in the labor market for working age adults, using data from the Life in Transition Surveys (LiTS) conducted in 2006. We decompose the observed inequalities into components that are attributable to circumstances an individual was born into (e.g., gender, parents’ education, minority status, etc) and other characteristics (education and age). We conduct additional exercises with this measure, which examine: (i) comparisons with an expenditure-based measure of inequality of opportunity; (ii) the extent to which the measures of inequality resonate with individual perceptions of life satisfaction and fairness; and (iii) how the results for ECA countries compare with similar measures in the Latin America and the Caribbean (LAC) region. Our findings show substantial inequality of opportunity (attributable to circumstances that an individual was born into) in employment status in the ECA region and a high degree of heterogeneity across countries in the circumstances that matter the most for inequality. The correlations between measures and perceptions of inequality among citizens across ECA countries suggest that inequality between groups, including measures of inequality of opportunity, matter more than overall measures of inequality for citizen perceptions of "fairness". The results are robust to different definitions of jobs as opportunities.